Ethnic renewal in Philadelphia's Chinatown : space, place, and struggle - Wilson, Kathryn E. (Kathryn Elizabeth), 1963- (Urban life, landscape, and policy., 2015)
Kathryn E. Wilson is Associate Professor of History at Georgia State University.